Challenging high-tech solutionism in an era of polycrisis: A commentary on claims for novel foods and on building an alternative narrative - Sage, Colin (The International Journal of Sociology of Agriculture and Food, 2024)
Considering the contemporary global landscape of interlocking environmental, economic and political challenges - labelled as a polycrisis - the paper takes issue with an influential narrative of technological solutionism. Both within the rapidly digitalizing agricultural sector that is reshaping industrial farming and across the novel foods category engaged in scaling protein production, there is a tendency to proclaim new technologies as providing singular remedies to existential problems. While conceding that new technologies may have an important role to play as we navigate uncertainty in striving for healthy, sustainable diets, this commentary argues that such efforts ought to be informed by a wider vision embracing complexity and scientific humility and capable of scrutinising the purpose of such innovations while ensuring the inclusion of valued social and cultural attributes of food. Ultimately, challenging dominant narratives of technological solutionism requires civil society to develop alternative discourses that speak to human and ecological wellbeing above purely technocratically defined objectives.